(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This study examines the development trends of commercial banks’ active operations in Uzbekistan, with a particular focus on the role of the National Bank. The analysis highlights the growing importance of credit operations, investment activities, and interbank placements in shaping the structure of banking assets. Special attention is given to the strategic measures undertaken to enhance human capital, including the establishment of corporate academies and large-scale investments in staff training, which improve institutional efficiency and align banking practices with international standards.